1988
DOI: 10.1002/ijc.2910420206
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of ebv markers in the clinical management of nasopharyngeal carcinoma (NPC): A multicenter follow‐up study

Abstract: Between December 1979 and April 1982, 373 patients with untreated, undifferentiated carcinoma of the nasopharynx (NPC), 99 in Hong Kong, 120 in Tunis and 154 in Villejuif, entered a longitudinal study aimed at determining the clinical prognostic value of EBV serology after radiotherapy. A minimum of 3 years' follow-up was achieved for 319 patients (83 in Tunis, 95 in Hong Kong and 141 in Villejuif) who had regular clinical and serological testing at intervals of 6-8 months. No significant difference in initial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
60
1

Year Published

1991
1991
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(63 citation statements)
references
References 12 publications
1
60
1
Order By: Relevance
“…Subsequent studies showed that NPC patients have elevated IgG and IgA antibody titers to the EBV viral capsid antigen lgA and early antigen, as well as increased IgG against the latent viral nuclear antigens 1 and 2 (EBNA-1, EBNA-2) and neutralizing antibodies against EBV-specific DNase (62)(63)(64)(65)(66)(67)(68)(69)(70)(71)(72)(73)(74). Moreover, these antibody titers, especially of IgA, precede tumor development by several years (75) and are correlated with tumor burden, remission, and recurrence (76)(77)(78)(79)(80)(81)(82)(83)(84). Based on these patterns, antibody against viral capsid antigen is now established as the basis of a screening test for NPC in high-risk populations (85)(86)(87)(88)(89)(90), particularly in combination with anti-EBV DNase antibodies (73,91).…”
Section: Risk Factorsmentioning
confidence: 99%
“…Subsequent studies showed that NPC patients have elevated IgG and IgA antibody titers to the EBV viral capsid antigen lgA and early antigen, as well as increased IgG against the latent viral nuclear antigens 1 and 2 (EBNA-1, EBNA-2) and neutralizing antibodies against EBV-specific DNase (62)(63)(64)(65)(66)(67)(68)(69)(70)(71)(72)(73)(74). Moreover, these antibody titers, especially of IgA, precede tumor development by several years (75) and are correlated with tumor burden, remission, and recurrence (76)(77)(78)(79)(80)(81)(82)(83)(84). Based on these patterns, antibody against viral capsid antigen is now established as the basis of a screening test for NPC in high-risk populations (85)(86)(87)(88)(89)(90), particularly in combination with anti-EBV DNase antibodies (73,91).…”
Section: Risk Factorsmentioning
confidence: 99%
“…Hao Chen 1& ,Yao-Ling Luo 1& , Lin Zhang 1 , Li-Zhen Tian 2 , Zhi-Ting Feng 3 , WanLi Liu 1 * commonly used in clinical diagnosis and screening of NPC (Henle et al, 1973;De et al, 1988;Zong et al, 1992). However, the lack of specificity of the VCA-IgA assay and sensitivity of the EA-IgA assay limits their effectiveness in NPC diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…Elevated antibody titers against EBV lytic antigens, representing EBV reactivation in vivo, correlate with advanced cancer stages, poor prognosis, or tumor recurrence of NPC (21,34). The serologic marker of EBV reactivation also serves as a risk factor of NPC (17).…”
mentioning
confidence: 99%